Peculiarities of Formation and Changes in the Rate of Tuberculosis Mortality in Altai Kray over Thirty-Year Period from 1991 to 2020 - E. A. Smetanina; A. G. Smetanin (Туберкулез и болезни лёгких)
The objective: to study the long-term changes (1991-2020) in tuberculosis mortality in population of Altai Kray and assess the impact of certain categories of citizens on the formation of this rate.Subjects and Methods: Statistical Forms no. 8, 30, and 33, statistical compilations, and medical scientific publications.Results. In order to analyze the curves reflecting changes in tuberculosis mortality in Altai Kray and Russia, these curves have been divided into three conventional periods. General trends have been identified but there are some peculiarities: a significant excess of the average longterm value of the rate versus this rate for whole of Russia; this rate increased faster in the conventional period of 1991-2005. Using the statistical method, it has been established that the formation of tuberculosis mortality rate in the population of Altai Kray was influenced by tuberculosis mortality rate in the Federal Penitentiary Service in 1997 and 1998 and in homeless people in 2005-2008.